HPTLC, HPTLC-MS/MS and HPTLC-DPPH methods for analyses of flavonoids and their antioxidant activity in Cyclanthera pedata leaves, fruits and dietary supplement. Issue 9 (15th June 2019) - Orsini, Francesca; Vovk, Irena; Glavnik, Vesna; Jug, Urška; Corradini, Danilo
Abstract: HPTLC silica gel, amino and C18 plates in combination with different developing solvents were explored for the first HPTLC chemical profiles of flavonoids and sugars in crude extracts from leaves and fruits of caigua ( Cyclanthera pedata Scrabs) harvested in Slovenia and Italy. New HPTLC and HPTLC-MS methods for analyses of flavonoids are based on HPTLC silica gel (preconditioned with water) or C18 plates in combination with developing solvents ethyl acetate–water–formic acid (17:3:2, v/v) or 5% formic acid in methanol-water (7:3, v/v), respectively. Detection was performed before (for flavonoids) and/or after post-chromatographic derivatization with Natural product (NP) reagent for flavonoids and diphenylamine-aniline-phosphoric acid (DAP) reagent for sugars. HPTLC–MS/(MS n ) analyses on silica gel and C18 stationary phases enabled tentative identification of several compounds in crude extracts from leaves and fruits. HPTLC-DPPH assay combined with image analyses and HPTLC–MS/(MS n ) analyses, applied for direct screening of antioxidant activity of separated chromatographic zones (compounds) on HPTLC silica gel plates, confirmed activity in several zones of all crude extracts, in which some active compounds were tentatively identified. Apigenin 6- C -glucoside (isovitexin) and luteolin 8- C -glucoside (orientin) were found in all crude extracts, but the last was the most active free radical scavenger. Both compounds were also identified in dietary supplement product produced from caigua fruits. Crude extracts from leaves showed much higher antioxidant activity than those from fruits. The highest antioxidant activity was determined for crude extract from leaves harvested in Slovenia, while among crude extract from fruits the highest activity was determined for the extract from fruits harvested in Italy. GRAPHICAL ABSTRACT: